The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
Handbook of Contemporary Neuropharmacology 2007
DOI: 10.1002/9780470101001.hcn025
|View full text |Cite
|
Sign up to set email alerts
|

Benzodiazepines

Abstract: Starting with a short overview on the pharmacology of Benzodiazepine (BZ) receptor ligands that includes aspects of their therapeutic actions, development of tolerance and dependence to BZ and their metabolism this review pays special attention to the interaction and mode of action of BZ with the various γ‐aminobutyric acid type A (GABA A ) receptors. We discuss the diversity of GABA A receptors with respect to the subunits, rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2012
2012
2012
2012

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 234 publications
0
4
0
Order By: Relevance
“…However, an α1, 2, 3, or 5 subunit and a γ subunit are required for high affinity binding of 1,4-BZs (and the other structurally distinct molecules discussed in this review) 1 . Hence, GABA A receptors containing an α 1,2,3, or 5 subunit have been referred to as “diazepam-sensitive” (DS), whereas receptor isoforms bearing an α 4 or α 6 subunit are referred to as “diazepam-insensitive” (DI) [8]. …”
Section: An Overview Of Gabaa Receptorsmentioning
confidence: 99%
See 3 more Smart Citations
“…However, an α1, 2, 3, or 5 subunit and a γ subunit are required for high affinity binding of 1,4-BZs (and the other structurally distinct molecules discussed in this review) 1 . Hence, GABA A receptors containing an α 1,2,3, or 5 subunit have been referred to as “diazepam-sensitive” (DS), whereas receptor isoforms bearing an α 4 or α 6 subunit are referred to as “diazepam-insensitive” (DI) [8]. …”
Section: An Overview Of Gabaa Receptorsmentioning
confidence: 99%
“…Subsequent studies have demonstrated that multiple amino acid residues on both the α and γ subunits can influence both the potency and efficacy of these molecules [8]. However, the ability to dramatically reduce the affinity of BZs by this His→Arg mutation was critical for a second wave of efforts to develop anxioselective agents.…”
Section: An Overview Of Gabaa Receptorsmentioning
confidence: 99%
See 2 more Smart Citations